Coping resources and strategies of Canadian ice-hockey players: An empirical National Hockey League career model - Battochio, R. C.; Stambulova, N. (International Journal of Sports Science & Coaching, 2019)
Sport psychology researchers have studied careers of Canadian ice hockey players in the National Hockey League (NHL) and devised an empirical NHL career model. The model was comprised of career stages, statuses, demands and barriers to career progression without any indication of coping. The intent in the present article is to feature coping resources and strategies utilized by players during each status and career stage within the empirical model. Five rookies, 5 veterans, and 13 retirees participated in conversational interviews and the data underwent a deductive thematic analysis. Prospects seeking to gain entry into the NHL set controllable expectations rather than playing to impress coaches and staff. Most prospects played in the minor leagues where they adjusted their expectations to accept roles that they were likely to have during an NHL call-up. The career stage of developing as an NHL player was about rookies producing immediately in their role while holding off internal competition for their roster spot. In the same stage, sophomores were in their second full NHL season and they studied their opponents to avoid the sophomore slump. The stage of reaching the NHL elite involved constant pressure for point production and winning playoff games. The final stage was about seasoned veterans maintaining NHL play involvement by preserving their physique despite being worn down from long careers in a contact sport. The authors will discuss the significance of the model for sport psychology researchers and practitioners, and NHL stakeholders.